2021
DOI: 10.1186/s13054-021-03644-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist as a weaning mode for adults with invasive mechanical ventilation: a systematic review and meta-analysis

Abstract: Background Prolonged ventilatory support is associated with poor clinical outcomes. Partial support modes, especially pressure support ventilation, are frequently used in clinical practice but are associated with patient–ventilation asynchrony and deliver fixed levels of assist. Neurally adjusted ventilatory assist (NAVA), a mode of partial ventilatory assist that reduces patient–ventilator asynchrony, may be an alternative for weaning. However, the effects of NAVA on weaning outcomes in clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 53 publications
0
4
0
2
Order By: Relevance
“…Student nurses are developing the required KA while undergoing critical nursing courses and theoretical lectures; however, there would be the possibility of failures in recognizing the clinical deterioration of patients connected with ventilators when they are placed for hospital training (14) . Above fifty percent of health care providers lack knowledge, especially about weaning criteria (15) and low skills in the physical assessment of a patient with ventilators (16) . Our results concerning student knowledge and attitudes discovered that more than seventy percent of students exhibited inadequate mechanical ventilator patient care knowledge in the pre-test.…”
Section: Resultsmentioning
confidence: 99%
“…Student nurses are developing the required KA while undergoing critical nursing courses and theoretical lectures; however, there would be the possibility of failures in recognizing the clinical deterioration of patients connected with ventilators when they are placed for hospital training (14) . Above fifty percent of health care providers lack knowledge, especially about weaning criteria (15) and low skills in the physical assessment of a patient with ventilators (16) . Our results concerning student knowledge and attitudes discovered that more than seventy percent of students exhibited inadequate mechanical ventilator patient care knowledge in the pre-test.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical data suggest that NAVA may facilitate weaning [ 93 ]—from a pathophysiological point of view, the prevention of diaphragmatic atrophy may be one of the mechanisms underlying this evidence [ 94 ]. In a clinical trial, the electrical activity of the diaphragm during NAVA was in the same range as a previous study linked to preserved muscular thickness [ 95 , 96 ].…”
Section: Nava—neurally Adjusted Ventilator Assistmentioning
confidence: 99%
“…Some recent systematic reviews and meta-analyses compared either NAVA alone or proportional modes (NAVA and PAV+) with conventional assist ventilation: Yuan et al included 7 studies suggesting that NAVA might be superior to PSV in difficult-to-wean patients [ 93 ]; Chen et al found a lower asynchrony index with NAVA vs. PSV and no significant differences in respiratory muscle unloading, with NAVA being associated with a significantly shorter duration of ventilation despite a similar ICU length of stay or mortality [ 121 ]; Kataoka et al found that the use of proportional modes was associated with a reduction in the incidence of asynchronies, weaning failure and duration of mechanical ventilation, compared with PSV; however, reduced weaning failure and duration of mechanical ventilation were found with only PAV and not NAVA [ 54 ].…”
Section: Clinical Use Of Nava In Acute Respiratory Failurementioning
confidence: 99%
“…Yuan et al (29) 2021 China La ventilación con el modo de asistencia ventilatoria ajustada neuralmente puede mejorar la tasa de éxito del destete en comparación con otros modos de asistencia parcial para pacientes de destetar. La evaluación de la duración de la ventilación mecánica, los días sin ventilación en el día 28, la mortalidad hospitalaria y el éxito de la extubación fueron favorables a la asistencia ventilatoria ajustada neuralmente.…”
Section: Año País Conclusionesunclassified